Intellect in Love: the Unifying Ground of Augustine’s Doctrine of God (宗教与历史 （ISSN: 3068-4803）, 2026)
This paper challenges the two dominant interpretive models in Augustinian scholarship—Gilson’s progressive model and Flasch’s rupture model—arguing instead that Augustine’s doctrine of God is governed from the outset by a dual structure of intellect and love that is mutually constitutive and irreducible to either term alone. Through an examination of Augustine’s theory of Ideas, his understanding of God as caritas, and the psychological analogy of the Trinity in De Trinitate VIII–IX, the paper shows that intellect already contains love within its own self-relation, while love, though primary as the unifying principle of the divine being, remains intrinsically ordered toward knowledge. This structure extends beyond the doctrine of God itself: in creation, love and intellect cooperate as efficient and formal causes respectively; in election, the same structure governs the order of salvation. Augustine’s vision is ultimately a unified theological vision in which knowing God is inseparable from loving participation in divine life—one that resists both the subordination of love to intellect and the reduction of the divine will to arbitrariness.